Corruption and access to socio-economic services in Africa - Andreas Freytag; Muhammad Faraz Riaz (Friedrich Schiller University Jena, 2021)
Corruption is one of the world's most widespread political problems. It can be found on international, national and sub-national level. Access to education and other socio-economic services is of utmost importance for all humans. It is still not exclusively based on merit, but often rather unfairly distributed and allocated depending on corrupt local bureaucrats. We utilize a micro level measure of corruption based on the personal experiences of individuals, which realistically represents the linkage between individuals and public office holders. For the empirical analysis, we utilized the Afrobarometer survey of 36 African countries that contains information of more than 50,000 citizens. Corruption is found being negatively correlated with the access to water, education, health and paved roads, while positively associated with access to sewage system and having no significant association with access to electricity grid. The findings reveal that in order to expand the access to basic socioeconomic services, governments need to control corruption in public offices on a daily basis.
Keywords: H1; K4; O1; O5; P4; 330; Development; Corruption; Local Services